Age‐related differences in responses to hydrogen sulfide in the bladder of spontaneously hypertensive rats. (5th January 2021) - Zou, Suo; Shimizu, Takahiro; Yamamoto, Masaki; Shimizu, Shogo; Higashi, Youichirou; Karashima, Takashi; Saito, Motoaki
Abstract : Objectives: To investigate whether a response to hydrogen sulfide donors (GYY4137 and sodium hydrosulfide) and the endogenous hydrogen sulfide system (hydrogen sulfide level and expression of cysteine aminotransferase, cystathionine β‐synthase, cystathionine γ‐lyase, and 3‐mercaptopyruvate sulfurtransferase) in the spontaneously hypertensive rat bladder differ with age, we compared the responses of hydrogen sulfide donors to micturition and bladder relaxation, and the endogenous hydrogen sulfide system in the bladder of 18‐week versus 12‐week‐old spontaneously hypertensive rats. Methods: GYY4137 was intravesically administered and cystometry was performed in anesthetized rats. The responses of sodium hydrosulfide were evaluated in carbachol‐mediated precontracted bladder strips. Bladder hydrogen sulfide levels and expression levels of each enzyme were investigated using the methylene blue method and Western blotting, respectively. Results: GYY4137 treatment significantly prolonged intercontraction intervals only in 12‐week‐old rats. Sodium hydrosulfide‐induced bladder relaxation was significantly attenuated in the strips of 18‐week‐old rats compared with that in 12‐week‐old rats. In the bladder dome, significant increases in hydrogen sulfide levels and in the expression of cystathionine β‐synthase, 3‐mercaptopyruvate sulfurtransferase, and cysteine aminotransferase were observed in 18‐week‐old rats compared with 12‐week‐old rats. However, cystathionine γ‐lyase bands were not detected in bladder tissues of either group. Conclusions: Bladder relaxation induced by hydrogen sulfide may be attenuated in spontaneously hypertensive rats in an age‐dependent manner.